Dual structure evolution of a Ag(i) supramolecular framework triggered by anion-exchange: replacement of terminal ligand and switching of network interpenetration degree12. Issue 74 (25th August 2016) - Li, Cheng-Peng; Wang, Si; Guo, Wei; Yan, Yan; Du, Miao
Abstract : Dual single-crystal to single-crystal transformations triggered by different anion-exchanges are achieved for a Ag(i ) coordination framework, where switching of network interpenetration degree is observed. Abstract : A 3-fold interpenetrated Ag(i ) coordination framework can exhibit dual structure evolution behaviours driven by distinct anion-exchange courses in which irreversible single-crystal to single-crystal transformation occurs, resulting in a switching of network interpenetration degree (from 3-fold to 2-fold).